2022
DOI: 10.1038/s41467-022-31946-5
|View full text |Cite
|
Sign up to set email alerts
|

Defunctionalizing intracellular organelles such as mitochondria and peroxisomes with engineered phospholipase A/acyltransferases

Abstract: Organelles vitally achieve multifaceted functions to maintain cellular homeostasis. Genetic and pharmacological approaches to manipulate individual organelles are powerful in probing their physiological roles. However, many of them are either slow in action, limited to certain organelles, or rely on toxic agents. Here, we design a generalizable molecular tool utilizing phospholipase A/acyltransferases (PLAATs) for rapid defunctionalization of organelles via remodeling of the membrane phospholipids. In particul… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 59 publications
(89 reference statements)
0
3
0
Order By: Relevance
“…Alterations in the membrane structure documented in electron micrographs included rupture of the outer mitochondrial membrane, leaving exposed edges, and internal swelling and disruption of cristae [58]. These observations were supported by a study using HeLa cells in a culture treated with PLAAT3, which showed similar damage to the mitochondria, endoplasmic reticulum, and other organelles [59]. Such distinctive changes to the membranes were not observed in chick embryo or adult Galago (bush baby) lenses where high-resolution electron micrographs were available from the epithelium through the OFZ [86,87].…”
Section: Evidence Against Autophagy In Organelle Eliminationmentioning
confidence: 58%
See 1 more Smart Citation
“…Alterations in the membrane structure documented in electron micrographs included rupture of the outer mitochondrial membrane, leaving exposed edges, and internal swelling and disruption of cristae [58]. These observations were supported by a study using HeLa cells in a culture treated with PLAAT3, which showed similar damage to the mitochondria, endoplasmic reticulum, and other organelles [59]. Such distinctive changes to the membranes were not observed in chick embryo or adult Galago (bush baby) lenses where high-resolution electron micrographs were available from the epithelium through the OFZ [86,87].…”
Section: Evidence Against Autophagy In Organelle Eliminationmentioning
confidence: 58%
“…Another related finding is the link between phospholipase A/acyltransferases (PLAATs) [57] and the elimination of lens organelles [58]. The translocation of PLATT enzymes to the phospholipid membranes of mitochondria causes the deformation of the mitochondrial surface and the subsequent loss of mitochondrial membrane potential [59]. While depolarization of the mitochondria is not induced when PI3K activity is suppressed [43], the mitochondria become depolarized during lens development just prior to the time that they are delivered to the autophagosomes for elimination [60].…”
Section: Signaling Regulators Control the Induction Of Autophagy To F...mentioning
confidence: 99%
“…PLAAT3 was reported to degrade organelle membranes at the terminal stages of lens development [58]. Moreover, engineered versions of PLAAT members can disrupt mitochondria and peroxisomes in vivo [59]. Interestingly, PLAATs show significant sequence homology to LRATs that, as mentioned earlier, display phospholipid‐dependent acyltransferase activity [60].…”
Section: Putative Roles Of Pdats In Membrane Lipid Remodeling and Org...mentioning
confidence: 99%